МЕТОДИКА ІДЕНТИФІКАЦІЇ ПАРАМЕТРІВ ПРУЖНОЇ МОДЕЛІ ВАЛОПРОВОДУ ТУРБОАГРЕГАТУ ДЛЯ МОДЕЛЮВАННЯ КРУТИЛЬНИХ КОЛИВАНЬ - Куєвда, Ю.В.; Балюта, С.М. (Інститут електродинаміки Національної академії наук України, 2017)
The mathematical models of different dimensions with a finite number of degrees of freedom of a powerful turbine-generator shaft, which is used to calculate the torsional vibrations of the shaft train, were compared. The computational studies of transients during switching of the turbine-generator to parallel operation with the electrical system with no-load conditions using different mathematical models of the shaft train and comparison of torsional moments were performed. The method of parameter identification for the multi-mass model of the shaft line of the turbine set using an iterative conjugate gradient method and a heuristic genetic algorithm was developed. The performed computational studies have shown efficiency of the developed technique. References 12, figures 6.